Searle y el significado literal - Acero, Juan José (Revista de Filosofía, 2007)
In his analysis of literal meaning Searle has deployed the principle that in carrying out an speech act the literal meaning of its words leaves undetermined the speech act’s content. It is argued that this principle not only goes against certain basic linguistic intuitions, but it also leads to unnecessary convoluted analysis of phenomena like the existence of non-articulated constituents and semantic transference. Lastly, it is shown that by putting together ideas of Wittgenstein and Dretske better explanations of those phenomena can be obtained.